KENAKALAN REMAJA YANG MENGKONSUMSI MINUMAN KERAS (Studi Kasus : di Kampung Pasar 60 Nagari Tapan Kabupaten Pesisir Selatan) - -, Rahmawati - (Pendidikan Sosiologi, 2014)
The background of this research because there are teenagers who do mischief like consuming liquor in a game of billiards in the village of Market 60. Availability of wrought-place game of billiards that facilitate adolescents to consume liquor in the place of the billiard game, what else shop owner provides a place for teens to consume liquor. The purpose of this penelitiaan are: 1) to describe the factors of juvenile delinquency in the village of Nagari Tapan Market 60 South Coastal District, 2) describe the effects of adolescent alcohol consumption. The theory used is Deferential Associaton theory developed by Edwin Sutherland, and research subjects are taken using the technique of sampling were 18 informants porposive research. The technique of collecting data through observation, interviews, document study. The research data analysis techniques using interactive data analysis methods, namely 1) Data collection, 2) data reduction, 3) Presentation of data, 4) Withdrawal conclusions. Location of the study was conducted in the village of Nagari Tapan Market 60 South Coastal District. Based on the results obtained the following conclusions: faktok adolescent alcohol consumption: 1) open access to get liquor, 2) Call for Friends sepermaina, 3) Personal Problems, 4) Disappointed with family, 5) Removing Boredom. The impact of adolescent drinking, 1) set aside by friends, 2) in putusi by boyfriend.